Changes in Health Indicators of Welfare in Group-Housed Shelter Cats - Vojtkovská, Veronika; Voslářová, Eva; Večerek, Vladimír (Frontiers in Veterinary Science, 2021)
The aim of this study was to detect changes in health-oriented welfare indicators of shelter cats housed in a shelter by means of long-term monitoring of health indicators of welfare in a population of group-housed cats in a private, no-kill shelter in the Czech Republic. The cat population housed in a large group was monitored for one year. The data recording took place at two-week intervals. A total of 220 cats were evaluated using a protocol containing 8 health-oriented welfare indicators: body condition, third eye visibility, eye discharge, eye irritation, nose discharge, the presence of pathologically induced respiratory sounds, coat condition, and lameness and abnormal posture. The assessment was performed based on the observation by two trained evaluators. The cats' condition was rated on a 5-point scale for each indicator, where the optimal condition was represented by the score of 1 and a severe deterioration by the score of 5 for the given indicator, except for the body condition indicator, where the optimal condition was represented by the score of 3. A deterioration in the score in at least one of the indicators during the stay in the shelter was recorded in 52 (41.6%) of 125 cats that were assessed at least twice. The effect of the LOS, sex and age on the scores for each health indicator was examined via a linear mixed model analysis, as this method allows for handling of dependencies in the data of repeated measurements. The effect of predictors on the third eye visibility scores was not found. The age of cats predicted the coat condition and body condition scores. The LOS predicted scores of the abnormal posture and lameness indicator and scores of a composite index composed of indicators related to upper respiratory tract disease. The results suggest that despite the fact that some improvement of health was documented during the cats' stay in the shelter, there were a non-negligible number of animals experiencing a permanent or long-term deterioration in health. Efforts to minimize the undesirable factors contributing to the deterioration of well-being of cats during their stay in a shelter should be made.